Doctrine of khiyar al-ayb (option caused by defect) as proposed by Muslim jurists and its maqasid in Islamic transaction - Awang Hamat, Mohd Afandi (Usuli Faqih Research Centre, 2015)
Islam is the religion revealed by Allah swt and therefore one of the most important aspect of religion is justice. Thus, Islam stresses on the importance of justice in all elements of it in regard to various injunctions revealed by Allah. This paper attempts to explain the meaning and doctrine of khiyar al-Ayb as highlighted by Sunni Muslim jurists of four different schools of law. As proposed by Muslim jurists, al-ayb implies a latent fault, flaw, blemish or defect, which exists in the goods at the time of contract taking place, and substantially impairs the value of the goods to the recipient. On account of defective products, is the buyer consequently has the right of option either to ratify the contract with full payment or revoke it entirely? Is the buyer may also accept the goods and ask for compensation or (al-irsh) on the possible loss due to such defect? Is the any conditions for the buyer to revoke his contract on the account of defective products that he or she has purchased? This paper will try to answer all of these questions by highlighting various issues in khiyar al-ayb starting from the definition of khiyar al-ayb, Legality of it, Conditions for valid option in respect to khiyar al-ayb as mentioned by Muslims jurists, and also maqasid behind the legality of khiyar al-ayb. This paper also will highlight about the irremovable and Persuasive or reasonable defect in regard to khiyar al-ayb as highlighted by our Muslim jurists. This paper will also explain about the views of Muslim jurists from different schools of Law in regard to Optional period in khiyar al-ayb, is it Immediately after the buyer notices about the defect (ala al-fawr), or is there any period of time in which the buyer having the right to revoke his transaction if there is any defects on his goods.